Mathematical representation ability based on learning styles of students on Anchored Instruction assisted Problem Card - Lastriani, Kartika Septina; Safa'atullah, Muhammad Fajar (Unnes Journal of Mathematics Education, 2019)
Learning outcomes and abilities of class VIII students of SMP Negeri 1 Banyubiru on the aspects of mathematical representation are not optimal. Each student has a different learning style that influences the process of representing mathematical problem solving. In this study, the application of the Anchored Instruction model assisted by Problem Card aims to find out students 'classical completeness and describe the students' mathematical representation abilities for each type of learning style, namely Visual, Auditorial, and Kinesthetic (V-A-K). This research method is mixed methods or combination methods. The research design used was explanatory sequential design. The subjects of this study were 9 students of class VIII B of SMP Negeri 1 Banyubiru who were selected using the purposive sampling method. Data collection techniques in this study used the test method, questionnaire method, and interview method. The results showed (1) the learning outcomes on the aspect of mathematical representation ability in the Anchored Instruction model achieved classical; (2) learning outcomes on aspects of mathematical representation ability for classes using the Anchored Instruction learning model aided by Problem Card are better than classes that use the Anchored Instruction learning model; (3) description of students' mathematical representation abilities for each type of learning style, namely visual, auditorial and kinesthetic.